Peningkatan Kedisiplinan Peserta Didik Melalui Model Pembelajaran Velue Clarification Technique Di Kelas IV Semester I SD Negeri Tingkir Tengah 02 Kota Salatiga Tahun Pelajaran 2023 - Wikanti, Yunda Arumi; Mawardi, Mawardi (JURNAL SINEKTIK, 2024)
The purpose of this research is improving the discipline of grade 4 students at SD Negeri Tingkir Tengah 02 Salatiga City for the 2023 academic year by using the Velue Clarification Technique learning technique. In this study using Classroom Action Research which consists of two cycles. This research used as subjects students in class IV Semester I at SD Negeri Tingkir Tengah 02, Salatiga City, academic year 2023 with a total of 26 students.. The data collection technique is observation, interviews, and documentation. Data analysis techniques using triangulation techniques and descriptions. Cycle I produced a 53.85% classical percentage and continued the research in Cycle II to obtain 80.77% classical results. From the results of data analysis, it can be concluded that the learning model using Velue Clarification Technique has succeeded in improving the discipline of class IV Semester I students at SD Negeri Tingkir Tengah 02, Salatiga City, for the 2023 academic year.